Physical performance and loading for six playing positions in elite female football: full‐game, end‐game, and peak periods. (22nd March 2021) - Panduro, Jeppe; Ermidis, Georgios; Røddik, Line; Vigh‐Larsen, Jeppe F.; Madsen, Esben Elholm; Larsen, Malte Nejst; Pettersen, Svein Arne; Krustrup, Peter; Randers, Morten B.
Abstract: The present study investigated the position‐specific match demands and heart rate response of female elite footballers, with special focus on the full‐game, end‐game, and peak‐intensity periods. In total, 217 match observations were performed in 94 players from all eight teams of the best Danish Women's League, that is, goalkeepers (GK, n = 10), central defenders (CD, n = 23), full‐backs (FB, n = 18), central midfielders (CM, n = 28), external midfielders (EM, n = 18), and forwards (FW, n = 11). Positional data (GPS; 10 Hz Polar Team Pro) and HR responses were collected. HRmean and HRpeak were 87%‐89% and 98%‐99% of HRmax, for outfield players, with no positional differences. CM, EM, and FB covered 8%‐14% greater ( P < .001) match distances than CD. EM, FW, FB, and CM performed 40%‐64% more ( P < .05) high‐speed running and 41%‐95% more ( P < .01) very‐high‐speed running (VHSR) than CD. From the first to the last 15‐minute period, total distance, except for FW, number of VHSR, except FB, peak speed and sum of accelerations and sum of decelerations decreased ( P < .05) for all outfield positions. In the most intense 5‐minute period, EM, FB, and CM performed 25%‐34% more ( P < .01) HSR than CD, whereas EM, FW, and FB performed 36%‐49% more ( P < .01) VHSR than CD. In conclusion, competitive elite female matches impose high physical demands on all outfield playing positions, with high aerobic loading throughout matches and marked declines in high‐speed running and intense accelerations and decelerations toward the end of games. Overall physical match demands are much lower for central defenders than for the other outfield playing positions, albeit this difference is minimized in peak‐intensity periods.